12-O-tetradecanoylphorbol 13-acetate-inducible proteins are synthesized at an increased rate in Bloom syndrome fibroblasts. - Mallick, U (1982)
A set of proteins, which in normal fibroblasts were barely, if at all, detectable, were synthesized at an increased rate in fibroblasts from patients with Bloom syndrome (BS). The same set of proteins was induced in normal human fibroblasts by treatment with 12-O-tetradecanoylphorbol 13-acetate (TPA). In BS cells, TPA caused a further 2-fold increase in the rate of synthesis. Production of these proteins was inhibited by the addition of fluocinolone acetonide to the culture medium. One of the proteins (XHF1) present at high levels in BS fibroblasts and in TPA-treated cells was also induced by irradiation with ultraviolet light. This protein was secreted into the culture medium. Most other TPA-inducible proteins were cytoplasmic. Among other human mutants prone to chromosome aberrations we found one of three tested cases of Fanconi anemia and one case of ataxia-telangiectasia that showed increased spontaneous rates of synthesis of the TPA-inducible proteins. In these cases, however, the induction by TPA was like that seen in healthy fibroblasts.